1987
DOI: 10.1017/s0950268800066607
|View full text |Cite
|
Sign up to set email alerts
|

Egg-grown and tissue-culture-grown variants of influenza A (H3N2) virus with special attention to their use as antigens in seroepidemiology

Abstract: SUMMARYA field strain of influenza A (H3N2) virus isolated in embryonated eggs during the 1984-5 influenza outbreak (A/Finland/13/85E) was compared in an antigenic analysis with virus from the same clinical specimen isolated in MDCK cell cultures (A/Finland/13/85M). The M-virus appeared to be more sensitive to haemagglutination-inhibiting antibodies against heterologous viruses than did the Evirus. The results of propagation and plaque purification experiments support the hypothesis that a single clinical spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“… 32 34 The extent to which seasonal vaccines that are fully derived and manufactured in mammalian cell culture will provide improved VE over egg-manufactured influenza vaccines remains to be determined, as definitive comparative field trials have not been reported yet, but animal and human serological testing suggests that mammalian cell-derived antigen could be, at the least, more protective – in certain seasons – particularly with respect to A(H3N2) and B vaccine components. 22 , 35 37 …”
Section: Cell-based and Recombinant Influenza Vaccinesmentioning
confidence: 99%
“… 32 34 The extent to which seasonal vaccines that are fully derived and manufactured in mammalian cell culture will provide improved VE over egg-manufactured influenza vaccines remains to be determined, as definitive comparative field trials have not been reported yet, but animal and human serological testing suggests that mammalian cell-derived antigen could be, at the least, more protective – in certain seasons – particularly with respect to A(H3N2) and B vaccine components. 22 , 35 37 …”
Section: Cell-based and Recombinant Influenza Vaccinesmentioning
confidence: 99%
“…Among the influenza vaccine studies employing increased doses of vaccine and booster vaccine strategies, a large randomized multi-center trial in long-term care facilities conducted in 1997-1998 by the present research group did not allow firm conclusions to be formed, mainly because the serological analysis by the ELISA technique precluded a proper comparison of the results with earlier findings on the protective effects of the vaccine [Roos-van Eijndhoven et al, 2001]. Therefore, all original serum samples from this large randomized multi-center trial in long-term care facilities were re-analyzed by hemagglutination inhibition assay (HAI), a generally accepted method to evaluate influenza vaccine responses [Pyhä lä et al, 1987;Meyer et al, 1993;Beyer et al, 2004] to the predominant subtype A/H3N2 strain of that season [Nichol et al, 2007].…”
Section: Introductionmentioning
confidence: 94%
“…Because influenza A/H3N2 is the predominant virus subtype since 1968, (HAI) to the A/H3N2 strain was performed. The assay conditions included using turkey erythrocytes for agglutination, a filtrate of Vibrio cholerae fimbriae as source of receptor destroying enzyme and four hemagglutinating units of the vaccine strain A/Nanchang/933/95 (H3N2), which was propagated on Madine Darby canine kidney cells [Kelly et al, 2004], a method well comparable or superior to earlier methods employing egg-grown virus [Palmer et al, 1975;Pyhä lä et al, 1987;Meyer et al, 1993].…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…Differences in HI titer are sometimes attributed to changes in the hemagglutinin sequence after viruses are passaged in eggs [8,18] or to changes in the neuraminidase sequence which may contribute to hemagglutination [7]. Supporting the notion that egg-adaptation alters the virus, higher HI titers were observed in an epidemiological study where human sera were tested with cellpropagated virus than with egg-propagated virus [19]. Interestingly, when egg-adapted viruses are further cultured in MDCK cells the virus often retains the egg-like serological characteristics and do not revert back to the cell-like characteristics [20].…”
Section: Introductionmentioning
confidence: 99%